Amygdalar enlargement in patients with temporal lobe epilepsy. Issue 6 (3rd November 2010) - Mitsueda-Ono, Takahiro; Ikeda, Akio; Inouchi, Morito; Takaya, Shigetoshi; Matsumoto, Riki; Hanakawa, Takashi; Sawamoto, Nobukatsu; Mikuni, Nobuhiro; Fukuyama, Hidenao; Takahashi, Ryosuke
Abstract : Objective: The purpose of the study was to clarify the significance of amygdalar enlargement (AE) in patients with temporal lobe epilepsy (TLE) detected by MRI. Methods: 11 TLE patients (eight men, mean age 45.3 (SD 18.2) years) with AE treated at Kyoto University Hospital were studied. Clinical history, ictal semiology, EEG, fluorodeoxyglucose–positron emission tomography (FDG-PET), interictal single photon emission CT (SPECT) and MRI were investigated. Amygdalar volume measured by 3 T MRI and its laterality index (LI) were compared with the three other groups: normal controls, patients with partial epilepsy of non-TLE and mesial TLE with hippocampal sclerosis (HS). Results: Average age of onset was 39.8 years (SD 19.5). Eight had complex partial seizures and three had generalised seizures. Epileptiform discharges were found in the temporal area ipsilateral to the AE by EEG. Interictal FDG–PET/SPECT revealed regional hypometabolism or hypoperfusion in the ipsilateral temporal area. MRI showed AE on the right in five patients, on the left in five and bilateral in one, all without apparent HS. Ten of 11 patients were diagnosed as unilateral TLE ipsilateral to the AE by neurophysiological and neuroimaging methods. Enlarged amygdalae showed iso- to slightly high intensity in FLAIR images without enhancement. Unilateral AE was not seen in the other three groups for amygdalar volume and LI (p<0.05). Discussion: AE is most likely a subtype of TLE without ipsilateral HS. This possibility of AE should be considered in TLE patients if there is no apparent HS.